Chitosan sulfate-lysozyme hybrid hydrogels as platforms with fine-tuned degradability and sustained inherent antibiotic and antioxidant activities. (1st September 2022) - Aguanell, Antonio; del Pozo, María Luisa; Pérez-Martín, Carlos; Pontes, Gabriela; Bastida, Agatha; Fernández-Mayoralas, Alfonso; García-Junceda, Eduardo; Revuelta, Julia
Abstract: The control of the properties and biological activities of chitosan-lysozyme hybrid hydrogels to exploit their interesting biomedical applications depends largely on the chitosan acetylation pattern, a difficult parameter to control. Herein, we have prepared sulfated chitosan-lysozyme hydrogels as versatile platforms with fine-tuned degradability and persistent bactericidal and antioxidant properties. The use of chitosan sulfates instead of chitosan has the advantage that the rate and mechanisms of lysozyme release, as well as antibacterial and antioxidant activities, depend on the sulfation profile, a structural parameter that is easily controlled by simple chemical modifications. Thus, while 6- O -sulfated chitosan hydrogels allow the release of loaded lysozyme in a short time (60% in 24 h), due to a high rate of degradation that allows rapid antibiotic and antioxidant activities, in 3- O -sulfated systems there is a slow release of lysozyme (80% in 21 days), resulting in long-lasting antibiotic and antioxidant activities. Graphical abstract: Unlabelled Image